2020
DOI: 10.1038/s41467-020-16432-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the origin of high-grade serous ovarian cancer using CRISPR-modification of mouse organoids

Abstract: High-grade serous ovarian cancer (HG-SOC)-often referred to as a "silent killer"-is the most lethal gynecological malignancy. The fallopian tube (murine oviduct) and ovarian surface epithelium (OSE) are considered the main candidate tissues of origin of this cancer. However, the relative contribution of each tissue to HG-SOC is not yet clear. Here, we establish organoid-based tumor progression models of HG-SOC from murine oviductal and OSE tissues. We use CRISPR-Cas9 genome editing to introduce mutations into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
95
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 55 publications
(64 reference statements)
2
95
0
Order By: Relevance
“…The HGSC cell-of-origin remains controversial. Transcriptomic (33,52,53), proteomic (54), epigenomic (52), and mouse modeling (31,55,56) data suggest that at least some cases initiate in OSE, but most often, HGSC initiates in FTE (33,57,58). Consequently, we focused our models on FTE organoids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HGSC cell-of-origin remains controversial. Transcriptomic (33,52,53), proteomic (54), epigenomic (52), and mouse modeling (31,55,56) data suggest that at least some cases initiate in OSE, but most often, HGSC initiates in FTE (33,57,58). Consequently, we focused our models on FTE organoids.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, while our manuscript was in review, others reported that FTE ("oviductal" in their manuscript) and OSE organoids engineered with the same genetic abnormalities could give rise to HGSC, although OSE-derived tumors could only be established orthotopically after an initial sub-cutaneous passage. This study was restricted to Tp53 -/-;Brca1 -/+ ;Pten -/and Tp53 -/-;Brca1 -/+ ;Nf1 -/combinations, which are not frequently seen in human HGSC, and used organoids from B6 x 129 mice, precluding transplantation into immune competent recipients and analysis of the TME (56).…”
Section: Discussionmentioning
confidence: 99%
“…This could be further corroborating the hypothesis that DDR could be more impacted in FI-like tumors, thus increasing genomic instability and conferring better response to platinum therapy in patients affected by this tumor subtype. Indeed, recent in vivo studies are showing better response to carboplatin/paclitaxel treatment for FI-derived tumors [ 55 , 61 ]. This is consistent with the better prognosis of patients affected by FI-like tumors in the IEO cohort, the latter being characterized by patients treated homogeneously with standard carboplatin/paclitaxel regimens.…”
Section: Discussionmentioning
confidence: 99%
“…There is now strong evidence that high-grade serous ovarian cancer (HGSOC) arises from both the distal fallopian tube surface epithelium (FTSE) and the ovarian surface epithelium (OSE) as the result of genomic events that activate signal transduction systems and metabolic pathways that sustain the transformed state (2,3). The WNT/β-catenin pathway is one of the signal transduction systems that is commonly activated in HGSOC, and the increase in its activity has been linked to the proliferation, migration, metastasis and prognosis of these tumors (4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…The RSPOs are of particular interest because there is now a large body of evidence from lineage tracing studies in mice that two of their receptors, LGR5 and LGR6, are markers of stem cells in the gut, skin and other epithelia (11,15). Much less is known about stem cells in the OSE or FTSE, but lineage tracing in mice suggests that LGR5 marks a stem cell population in the ovary, and LGR6-expressing cells are found in organoids grown from human fallopian tube epithelium (2,3,16). Using data from The Cancer Genome Atlas (TCGA) we previously observed that HGSOC expresses unusually high levels of LGR5 and LGR6 mRNA.…”
mentioning
confidence: 99%